Electrospinning and Additive Manufacturing: Adding Three-Dimensionality to Electrospun Scaffolds for Tissue Engineering - Smith, James A.; Mele, Elisa (Frontiers in Bioengineering and Biotechnology, 2021)
The final biochemical and mechanical performance of an implant or scaffold is defined by its structure, as well as the raw materials and processing conditions used during its fabrication. Electrospinning and Additive Manufacturing (AM) are two contrasting processing technologies that have gained popularity amongst the fields of medical research i.e., tissue engineering, implant design, drug delivery. Electrospinning technology is favored for its ability to produce micro- to nanometer fibers from polymer solutions and melts, of which, the dimensions, alignment, porosity, and chemical composition are easily manipulatable to the desired application. AM, on the other hand, offers unrivalled levels of geometrical freedom, allowing highly complex components (i.e., patient-specific) to be built inexpensively within 24 hours. Hence, adopting both technologies together, appears to be a progressive step in pursuit of scaffolds that better match the natural architecture of human tissues. Here, we present recent insights into the advances on hybrid scaffolds produced by combining electrospinning (melt electrospinning excluded) and AM, specifically multi-layered architectures consisting of alternating fibers and AM elements, and bioinks reinforced with fibers prior to AM. We discuss how cellular behavior (attachment, migration, and differentiation) is influenced by the co-existence of these micro- and nano-features.